If two do the same thing-- comparing IHE Profiles PIX/PDQ based nn HL7 2.x and HL7 version 3 - Václavík, Marek (European Journal for Biomedical Informatics, 2012)
Background: IHE integration profiles for managing patient identification, PIX and PDQ, exist in two alternative forms: on the one hand using HL7 2.x, on the other hand based on HL7 Version 3. Objective: Knowing difierences between the competing integration profiles shall assist the user to choose the one better suitable for their specific deployment. Methods: Difierences in the set of interactions, the information model, the vocabulary and the required behavior of individual interactions were analyzed. Results: A list of specific features and constraints for each of the integration profiles was compiled. Conclusions: Not all of the identified deltas originate in the inherent incompatibility between HL7 2.x and 3.0, they also result from the specific constraints imposed by the IHE profile. Identified disparities include the communication pattern, constraints to identifier schemas and pseudonymization capabilities.
Keywords: referenční standardy; Reference Standards; Software; software; Medical Informatics; Information Systems; lidé; informační systémy; lékařská informatika; Humans